Neutral temperature for naturally ventilated residences in Kota Kinabalu, Sabah, Malaysia - Harimi Djamila (2012)
An extensive field study was carried out in naturally ventilated residential buildings in Kota Kinabalu, Sabah, Malaysia. Both survey questionnaires and measured physical indoor climates were adopted in the present investigation. A total of 890 responses over one whole year were gathered. The survey was designed as cross sectional data collection. The objectives were to predict and characterize occupant thermal perceptions in residences which included information about occupant’s adaptive preference use of building controls, compare observed and predicted percent of dissatisfied and discern differences between this study and similar studies in the humid tropics. Most of the subjects’ weights under investigation were normal. The average clothing insulation level worn by the subjects was found to be 0.3 clo which was less than that assumed in the standards during summer. Consequently, the non applicability of ASHRAE thermal comfort chart was highlighted. In terms of clothing patterns, it was found that adjustment of cloths worn by the occupants due to further increase of indoor air temperature in the future was less likely to occur in their dwelling. The mean thermal sensation of the groups showed a heightened sensitivity to temperature represented by a gradient of one sensation unit per 2.50C change in indoor air temperature with an optimum neutral temperature of 300C. At this optimum value, there will be at least 22% of occupants unsatisfied with the indoor air temperature. A clear contrast between methods in the determination of neutral temperature were found, discussed, and clarified. In addition, it was concluded that the effect of temperature and humidity level could not be separated as the two variables are highly correlated and people thermal sensation toward indoor air temperature seems not to be affected by the variation of humidity. Further, people were not able to separate between the effect of air movement and the effect of indoor air temperature in their thermal sensation to the indoor environment as the desire for coolness was expressed by stillness of the air movement. Overall, when considering the direct thermal acceptability, at least 80% of occupants found the indoor temperature acceptable within the range of 270C to about 320C. Preferred indoor temperature was 26.30C. Gender thermal perception was explored and differences were not ascribed to variance in their clothing insulation levels. Occupant’s thermal behavioural adaptation were investigated and compared with other studies. The results of this study can be used for building thermal design in naturally ventilated housing with thermal comfort approach. Occupant behaviour in their dwellings from this study provides also valuable information for building thermal design for Malaysian residences. As such, the better our understanding of occupant responses to the thermal indoor environment, the most likely passive strategies will be implemented intelligently to suit the occupant needs and it will be more meaningful to building designers. Such investigation is expected to benefit the wider academic community.